Composting olive mill pomace and other residues from rural southeastern Spain - Canet, Rodolfo; Pomares, Fernando; Cabot, B.; Chaves, C.; Ferrer, E.; Ribó, Marta; Albiach, Remedios (2017)
The costly disposal of the semisolid residual pomace generated in the two phase extraction used in modern olive mills is causing serious problems to the small oil producers of rural southeastern Spain. Composting may be a viable alternative since complementary residues are usually available in these areas to prepare an adequate starting mixture. In this work, four different combinations of residues (pomace + rabbit manure, pomace + sheep manure, pomace + rabbit manure + rice straw, pomace + rabbit manure + almond shells) were composted in 3 toil piles aerated by turnings, using technology available to any small community of oil producers. During the four long processes (9-10 months), a steady decrease of organic matter and increases in the concentrations of nutrient and humic substances were observed, together with large increases in pH and salinity which may reduce the agronomic value Of the final products.